Finite element analysis (FEA) of RC beams reinforced with natural fiber woven mats by abaqus - Chan, Kien Chong (2017)
Concrete was relatively strong in compression but weak in tension and tended to break. Traditionally, the deficiency in tension was defeated by the used of conventional internal steel reinforcement due to its extremely high tensile strength. However, steel has its problems such as high-energy consumption and cost during production, difficult for handling due to its high weight, easy to corrode in unfavorable situations. To overcome its drawbacks, the use of natural fiber reinforced polymer (NFRP) as an alternative material of conventional steel reinforcement has been observed. On account of its wide availability, eco-friendly, low production cost, low weight and high specific strength and corrosion resistance, NFRP was a promising internal reinforcement for concrete beam. In this study, the potential of kenaf fiber reinforced woven mat (KFRWM) and jute fiber reinforced woven mat (JFRWM) as internal reinforcement in concrete beam were investigated by using non-linear finite element analysis (FEA). Therefore, the aim of this research was to determine the behavior of concrete beam reinforced with KFRWM and JFRWM in term of load-deflection relationship and crack pattern as well as its effects on concrete beam through the finite element software, ABAQUS, 6.14. Finally, the finite element result was validated with the experimental result. There were a total of four types of beam model being simulated under three-point bending conduct, which included pure concrete beam and RC beam with steel reinforcement as control beam, RC beam with KFRWM and RC beam with JFRWM. According to the simulation result, it can be found out that the pure concrete beam and RC beam with KFRWM and JFRWM were subjected to flexural failure with only a flexural crack at the center of the beam, which failed before the beam yield. In terms of load-deflection response, there was a stiffness enhancement and an ultimate load increment of 54.14% and 46.68% when the pure concrete beam reinforced with KFRWM and JFRWM, respectively. Nevertheless, as compared to RC beam with steel reinforcement, which subjected to shear failure with the critical diagonal crack at the shear span, only half of the strength in term of ultimate load was achieved due to the insufficient strength of KFRWM and JFRWM to fully resist the flexural load from the beam. Thus, it can be concluded that KFRWM and JFRWM has only slightly improved the flexural strength of pure concrete beam by around 50.41%. A comparable agreement in terms of the load- deflection relationship and a good agreement in term of the crack pattern between numerical result and experimental result was achieved.